2018
DOI: 10.1101/468975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bipolar multiplex families have an increased burden of common risk variants for psychiatric disorders

Abstract: Multiplex families with a high prevalence of a psychiatric disorder are often examined to identify rare genetic variants with large effect sizes. In the present study, we analysed whether the risk for bipolar disorder (BD) in BD multiplex families is influenced by common genetic variants. Furthermore, we investigated whether this risk is conferred mainly by BD-specific risk variants or by variants also associated with the susceptibility to schizophrenia or major depression. In total, 395 individuals from 33 An… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
1
15
1
Order By: Relevance
“…Importantly, we were able to show that MDD PRS added to the predictive utility of two readily obtainable self‐report parameters of SA risk, personal (lifetime) and family history of MDD. Whereas it might have been expected that there would be a higher MDD PRS in those with a positive family history of MDD (Andlauer et al, 2021), it is noteworthy that MDD PRS added to the explanatory power of that self‐report parameter alone. The same is true of personal history of MDD, on which MDD PRS is trained.…”
Section: Discussionmentioning
confidence: 93%
“…Importantly, we were able to show that MDD PRS added to the predictive utility of two readily obtainable self‐report parameters of SA risk, personal (lifetime) and family history of MDD. Whereas it might have been expected that there would be a higher MDD PRS in those with a positive family history of MDD (Andlauer et al, 2021), it is noteworthy that MDD PRS added to the explanatory power of that self‐report parameter alone. The same is true of personal history of MDD, on which MDD PRS is trained.…”
Section: Discussionmentioning
confidence: 93%
“…Most PRS studies report shared genetic risk for different outcomes, e.g. risk for one disorder tends to increase risk for other disorders (Andlauer et al, 2019) or poor cognitive performance (Gialluisi et al, 2019). Instead, we found that PRS for schizophrenia were associated with better hearing.…”
Section: Discussionmentioning
confidence: 99%
“…PRS were calculated in R v3.33 using imput In each outer cross-validation instance, the cutoff producing the maximum sensitivity across three inner cross-validation folds was tested on the remaining fold. Nested cross-validation was repeated 100 times and the mean cutoff of the 100 repetitions was used as the final cutoff.ed genetic data, as described previously [44, 45]. For each PRS, the effect sizes of variants from the discovery-stage analyses (training data), below a selected discovery-stage p -value threshold, were multiplied by the imputed SNP dosage in the replication-stage test data and then summed to produce a single PRS per threshold.…”
Section: Methodsmentioning
confidence: 99%
“…PRS were calculated in R v3.33 using imput In each outer cross-validation instance, the cutoff producing the maximum sensitivity across three inner cross-validation folds was tested on the remaining fold. Nested cross-validation was repeated 100 times and the mean cutoff of the 100 repetitions was used as the final cutoff.ed genetic data, as described previously [44,45] For the prediction of the presence of nADA in the replication dataset, logistic regression of the eight PRS, the top single GWAS variant, and the top HLA allele from the discovery stage was conducted using the GWAS models. The area under the receiver operating characteristic curve (AUC) was calculated using the R package pROC, its 95 % confidence interval (CI) with the function ci.auc (2000 stratified bootstrap replicates).…”
Section: Polygenic Risk Scores (Prs) and Prediction Of Nadamentioning
confidence: 99%